1980
DOI: 10.1073/pnas.77.8.4623
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of active opiate receptors.

Abstract: Receptors that reversibly bind opiates and opioid peptides have been solubilized from brain and neuroblastoma-glioma hybrid cell NG108-15 membranes. Active receptors are specifically solubilized with a new type of detergent 3-[(3-cholamidopropyl)dimethylammonio}1-propanesulfonate, which is a zwitterionic derivative of cholic acid. The solubilized receptor complexes behave as large molecules with a Stokes radius of 70 A and contain protein as an essential constituent.A necessary first step in the study of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
2

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(80 citation statements)
references
References 15 publications
6
71
1
2
Order By: Relevance
“…A similar value of Mr is obtained by gel-exclusion chromatography (results not shown). It is noteworthy that Evans & Gurd (1973) have previously suggested that the mouse liver enzyme may be a dimer of two identical-size subunits (Mr 70000-75 000) in the native state, and that both Naito & Lowenstein (1981) (Hjelmeland, 1980;Simonds et al, 1980)}, suggesting that different zwitterionic detergents will be useful for the purification of different membrane proteins. Similarly, the use of a monoclonal-antibody immunoaffinity step will be specific to the protein of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A similar value of Mr is obtained by gel-exclusion chromatography (results not shown). It is noteworthy that Evans & Gurd (1973) have previously suggested that the mouse liver enzyme may be a dimer of two identical-size subunits (Mr 70000-75 000) in the native state, and that both Naito & Lowenstein (1981) (Hjelmeland, 1980;Simonds et al, 1980)}, suggesting that different zwitterionic detergents will be useful for the purification of different membrane proteins. Similarly, the use of a monoclonal-antibody immunoaffinity step will be specific to the protein of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, opiate receptors have been solubilized with full retention of their agonist specificity [47]. Another solubilised opiate receptor preparation retained the ability of Na ÷ to modify binding [48], although no effects of GTP were detected.…”
Section: Structural Studies On Dually Regulated Adenylate Cyclase Sysmentioning
confidence: 99%
“…Delta opiate receptor numbers were measured in membrane fractions by equilibrium radioligand binding analysis with 2 nM [3H]diprenorphine as previously described [20]. Specific binding is defined as the difference between the amount of radioactive ligand bound in the presence and absence of 10/.tM non-radioactive ligand after 10 min incubation at 37°C.…”
Section: Ligand Binding Assaymentioning
confidence: 99%